Long-term changes in mandibular bone microchemical quality after radiation therapy and underlying systemic malignancy: A pilot study - A. Palander (World Scientific Publishing, 2021)
Radiation therapy (RT) is a treatment option for head and neck cancer (HNC), but 2% of RT patients may experience damage to the jawbone, resulting in osteoradionecrosis (ORN). The ORN can manifest years after RT exposure. Changes in the local microchemical bone quality prior to the clinical manifestation of ORN could play a key role in ORN pathogenesis. Chemical bone quality can be analyzed using Fourier transform infrared spectroscopy (FTIR), that is applied to examine the effects of cancer, chemotherapy, and RT on the quality of human mandibular bone. Cortical mandibular bone samples were harvested from dental implant beds of 23 individuals, i.e., patients with surgically and radiotherapeutically treated HNC (RT-HNC, n=7), surgically and radiochemotherapeutically treated HNC (CH-RT-HNC, n=3), only surgically treated HNC (SRG-HNC, n=4), and healthy controls (n=9). Infrared spectra were acquired from two representative regions of interest in cortical mandibular bone. Spectral parameters, i.e., mineral-to-matrix ratio (MM), carbonate-to-matrix ratio (CM), carbonate-to-phosphate ratio (CP), collagen maturity (cross-linking), crystallinity, acid phosphate substitution (APS), and advanced glycation end products (AGEs), were analyzed for each sample. Amide I region of the CH-RT-HNC group differed from the control group in cluster analysis (p=0.02). Apart from a minor variation trend in collagen maturity (p=0.07), there were no other significant differences between the groups. Thus, the effect of radiochemotherapy on mandibular bone composition should be further investigated. In future trials, this study design is potential when the effects of the cancer burden and different HNC treatment modalities on jawbone composition are studied, in order to reveal ORN pathogenesis.